Control of an Unusual Photo-Claisen Rearrangement in Coumarin Caged Tamoxifen through an Extended Spacer - Wong, Pamela T; Roberts, Edward W; Tang, Shengzhuang; Mukherjee, Jhindan; Cannon, Jayme; Nip, Alyssa J; Corbin, Kaitlin; Krummel, Matthew F; Choi, Seok Ki (ACS chemical biology, 2017)
The use of coumarin caged molecules has been well documented in numerous photocaging applications including for the spatiotemporal control of Cre-estrogen receptor (Cre-ERT2) recombinase activity. In this article, we report that 4-hydroxytamoxifen (4OHT) caged with coumarin via a conventional ether linkage led to an unexpected photo-Claisen rearrangement which significantly competed with the release of free 4OHT. The basis for this unwanted reaction appears to be related to the coumarin structure and its radical-based mechanism of uncaging, as it did not occur in ortho-nitrobenzyl (ONB) caged 4OHT that was otherwise linked in the same manner. In an effort to perform design optimization, we introduced a self-immolative linker longer than the ether linkage and identified an optimal linker which allowed rapid 4OHT release by both single-photon and two-photon absorption mechanisms. The ability of this construct to actively control Cre-ERT2 mediated gene modifications was investigated in mouse embryonic fibroblasts (MEFs) in which the expression of a green fluorescent protein (GFP) reporter dependent gene recombination was controlled by 4OHT release and measured by confocal fluorescence microscopy and flow cytometry. In summary, we report the implications of this photo-Claisen rearrangement in coumarin caged compounds and demonstrate a rational linker strategy for addressing this unwanted side reaction.